2014
DOI: 10.1007/s10549-014-2890-1
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of breast cancer in BRCA-mutation carriers: a systematic review and meta-analysis

Abstract: This meta-analysis investigates the oncological safety of breast-conserving therapy BCT in BRCA-mutation carriers and the risk for contralateral breast cancer (CBC) compared with non-carriers, potential risk factors for ipsilateral breast recurrence (IBR) or CBC and grades these factors based on the level of evidence. A PubMed search was conducted through April 2013 to identify studies that described the risk for IBR and CBC after BCT in BRCA-mutation carriers versus non-carriers as well as studies that invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
124
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(135 citation statements)
references
References 42 publications
7
124
0
4
Order By: Relevance
“…Similar adaptations have been previously used in the meta-analysis of risk factors in breast cancer [16].…”
Section: Quality Assessmentmentioning
confidence: 98%
“…Similar adaptations have been previously used in the meta-analysis of risk factors in breast cancer [16].…”
Section: Quality Assessmentmentioning
confidence: 98%
“…On the other hand, another study reported higher mortality rates in mutation carriers at 116 months of follow-up (15,16).…”
Section: Right Lumpectomy + Slnbmentioning
confidence: 94%
“…In 10 of these, local recurrence rates following breast conserving surgery (BCS) in patients with and without the mutation were evaluated (15). The local recurrence rate was 17% in BRCA mutation carriers, while this rate was 11% in patients without BRCA mutation and this difference was not statistically significant (p=0.07).…”
Section: Right Lumpectomy + Slnbmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain genes mutations like BRCA1 and BRCA2 increase the risk of the disease (Valachis, 2014;Smith, 2011). BRCA1 and BRCA2 are human genes that produce tumor suppressor proteins.…”
Section: Introductionmentioning
confidence: 99%